Vascular Access Scenario in Italy: Evolution and Comparison by Two Surveys (1998-2013). Issue 5 (September 2016) - Bonucchi, Decenzio; Palmieri, Lucia; Arletti, Silvia; Cappelli, Gianni; Lomonte, Carlo; Lodi, Massimo; Meola, Mario; Spina, Monica; Napoli, Marcello
Purpose: Dialysis settings have generally improved over the last decades, but the vascular access setting did not see significant advances and experienced a progressive worsening in epidemiology and clinical features. The aim of the study was to describe and compare evolution of vascular access in Italy over time. Methods: A national survey implemented in Italy last year is presented and compared to a previous survey performed in 1998. Present survey collected data from almost 50% of centers involved in vascular access. Results: The nephrologist participates in the management of vascular access in 97% of centers. Almost 40% of centers declare more than 40% of central venous catheters (CVCs) at first dialysis with maximum value being 60%. Prevalence of CVCs is greater than 20% in chronic prevalent patients in 38.8% of centers. According to the 2013 survey, CVCs account for 51.6% of procedures, while arteriovenous fistulae (AVF) and prostheses represent 42.4% and 6%, respectively. Nephrologists perform 73% of procedures on CVCs. From 1998 to 2013, a sharp increase in CVC prevalence was seen, in both incident and prevalent dialysis patients. This activity, mostly due to CVC management, is almost completely carried by nephrologists. Discussion: The variability in CVC utilization among centers suggests the lack of a shared policy in patients and access coupling. Quantitative criteria should be used to reduce inappropriate strategy in vascular access creation. Since this activity in Italy is organized at a local level without a shared organizational model, we should inquire whether a system managed so well in the past should now be rebuilt on the model of organ transplantation.